2005
DOI: 10.1017/cbo9780511610431
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Success in Second Language Acquisition

Abstract: This clear and informative textbook is designed to help the student achieve optimal success as a language learner and user. Aimed at beginning to intermediate undergraduates and above, it teaches students to understand their own preferences in learning, to develop individual learning plans and approaches, and to select appropriate learning strategies. The authors - all leading experts in language teaching - base their advice on theories of learning, cognition, and memory, concepts which they explain in simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 46 publications
2
66
1
6
Order By: Relevance
“…Ehrman and Oxford () reported that less successful learners randomly use various strategies, while more successful learners systematically use specific strategies for specific tasks. This replicates aspects of a curvilinear pattern commonly found by L2 strategy researchers using the SILL: Advanced learners use fewer strategies than intermediate learners, advanced learners use a subset of their former strategies, and advanced learners use their select strategies in new, creative ways that relate to the complexities of advanced language learning (Green & Oxford, ; Hong–Nam & Leavell, ; Leaver, ; Oxford, ) . Research focused on reading skills has also shown the importance of using an effective subset of strategies (Kember & Gow, ).…”
Section: Discussionsupporting
confidence: 72%
“…Ehrman and Oxford () reported that less successful learners randomly use various strategies, while more successful learners systematically use specific strategies for specific tasks. This replicates aspects of a curvilinear pattern commonly found by L2 strategy researchers using the SILL: Advanced learners use fewer strategies than intermediate learners, advanced learners use a subset of their former strategies, and advanced learners use their select strategies in new, creative ways that relate to the complexities of advanced language learning (Green & Oxford, ; Hong–Nam & Leavell, ; Leaver, ; Oxford, ) . Research focused on reading skills has also shown the importance of using an effective subset of strategies (Kember & Gow, ).…”
Section: Discussionsupporting
confidence: 72%
“…They have argued that these factors influence a learner's willingness to take risks and interact in the L2 (Naiman, Fröhlich, Stern, & Todesco, 1978, ; Oxford & Erhman, ; Rubin, ). Early researchers predicted extraverts to be better language learners (as they may be more linguistically active both in and out of the classroom) but introverts can be equally effective, though they may take different routes (Leaver, Ehrman, & Shekhtman, ). Though introverts may take more time before jumping in to conversations, this does not mean that they do not participate actively when opportunities arise.…”
Section: Intercultural Sensitivitymentioning
confidence: 99%
“…They have been gathered and displayed in the table below. Ehrman, 1993Ehrman, , 1996Ehrman, , 1999Hartmann, 1991;Leaver et al, 2005) Thin ego boundary learners…”
Section: Profiles Of Thick and Thin Ego Boundary Fl Learnersmentioning
confidence: 99%